Adipositas Cordis in Two Cats with Sudden Death. (April 2020) - Parisi, F.; Vezzosi, T.; Saldaña, J.A. Mercado; Poli, A.
Summary: Adipositas cordis (AC) is a rare cardiomyopathy characterized by fatty infiltration of the myocardium without signs of tissue destruction or inflammation. Its diagnosis is challenging and requires histopathological examination. This study describes such cardiomyopathy in two cats that died suddenly. In both cases, anatomopathological examination showed gross lesions indicative of acute heart failure, associated with an increase in subepicardial fat, particularly in the right ventricle. Microscopically, there was an increased amount of subepicardial and intramyocardial adipose tissue in the right ventricular free wall, without signs of cellular degeneration, inflammatory infiltration, necrosis or fibrosis, confirmed by histochemical staining. AC is a rare cardiac pathology, but it should be taken into consideration in feline medicine when a sudden death occurs.